2019
DOI: 10.1051/epjconf/201920001014
|View full text |Cite
|
Sign up to set email alerts
|

Astronomy: learning theories applicable for education in planetarium environment

Abstract: How do people learn in general and study astronomy in particular? To develop a coherent educational policy we need an appropriate theory. Does learning consist of the incremental addition of individual “bits” of information into the mind? Or is learning an active process that transforms the mind of the learner? Among different theories on how people learn are: Behaviorism, Neuroscience, Right Brain vs. Left Brain, Communities of Practice, Control Theory, Observational Learning (Social learning theory), Vygotsk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(2 reference statements)
0
2
0
1
Order By: Relevance
“…Despite the growing number of large-scale space education programmes (Roche et al, 2021a), there remains some debate over the theories of learning underpinning astronomy and space education in informal environments (Kovalenko, 2019;Anjos and Carvalho, 2020). Constructivism is one of the most common theories of learning that provides the theoretical foundation for events where public audiences engage with science (Stocklmayer et al, 2010;McCauley et al, 2018), and for young people engaging in space and astronomy in informal learning environments, social constructivism-whereby learning is mediated through social interaction with teachers, educators, and peers-is often the learning theory that underpins the activities (Vygotsky, 1978;Kallery, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the growing number of large-scale space education programmes (Roche et al, 2021a), there remains some debate over the theories of learning underpinning astronomy and space education in informal environments (Kovalenko, 2019;Anjos and Carvalho, 2020). Constructivism is one of the most common theories of learning that provides the theoretical foundation for events where public audiences engage with science (Stocklmayer et al, 2010;McCauley et al, 2018), and for young people engaging in space and astronomy in informal learning environments, social constructivism-whereby learning is mediated through social interaction with teachers, educators, and peers-is often the learning theory that underpins the activities (Vygotsky, 1978;Kallery, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted by Kovalenko (2019) titled 'Astronomy: Learning Theories Applicable for Education in Planetarium Environment'. This research concluded that in an educational activity, there are important theories to be taught to learners, such as environmental science, neuroscience, left and right brain, community of practice, control theory, social learning theory, Vygotsky and social cognition, learning styles, Piaget's theory, constructivism, brain-based learning, multiple intelligences theory.…”
Section: Introductionmentioning
confidence: 99%
“…Este sistema inteligente usa tecnologias da informação criando um aprendizado adaptativo real. De forma esquematizada, foram propostas cinco dimensões e um número variável de táticas para cada dimensão.Na Ucrânia,Kovalenko (2019) defende que um planetário pode oferecer ao público, com diferentes tipos de inteligências, uma abordagem diferente usando as IM. Por exemplo, para a inteligência lógico-matemática cálculos, fórmulas, números e atividades de resolução de problemas.…”
unclassified